Diagnostic Accuracy of Modified Alvarado Score (MAS) and Ohmann Scores (OS) in Diagnosing Acute Appendicitis - Zahid Rasheed, Sauleha Sayyed, Imran Ali, Fawad Hameed, Muhammad Rizwan, Gul Naz, Natasha Kanwal Mirza, (Pakistan Journal of Medical & Health Sciences, 2023)
In the field of General Surgery AA is the frequent clinical condition for which patients who need emergency surgery present with abdominal pain.1 Diagnosis of this pathology is made with the help of history, patient symptoms, and clinical exam and lab investigations. Ultrasonography (USG) and computed tomography (CT) images for acute appendicitis should be considered.2 Methodology: The purpose of the study is to compare the diagnostic accuracy of Modified Alvarado Score (MAS) and Ohmann Scores (OS) in diagnosing the pathology of Acute Appendicitis, while retaining histopathology as the basis for final diagnosis. A total of 411 patients were admitted via the Accidents & Emergency Department of Mayo Hospital Lahore, meeting the inclusion and exclusion requirements having the clinical diagnosis of acute appendicitis. For each patient, both Modified Alvarado and Ohmann scores were assessed prior to undergoing the procedure, i.e. open appendectomy. Abdominopelvic assessments and laboratory results were assessed and abdominal USG was performed in all patients. Biopsy of the removed appendix was sent for histopathology to Pathology Department of King Edward Medical University. Results: For the modified Alvarado and Ohmann score; sensitivity and specificity of was 89.74%, 90.48%, 85.13% and 80.95% respectively. The positive predictive value (PPV) and negative predictive value (NPV) for “modified Alvarado score” was 99.43% and 32.2% and for “Ohmann score” it was 98.81% and 22.67% respectively. Conclusion: Both scoring system are sensitive and specific enough for diagnosis of acute appendicitis. However, sensitivity and specificity of modified Alvarado score is higher as compared to Ohmann score. Keywords: Acute Appendicitis, Diagnostic Accuracy, Modified Alvarado Score, Ohmann Score, Histopathology.